Systemy produkcji rolniczej a obciążenie środowiska naturalnego - Ziętara, Wojciech (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1999)
The paper provides the overall characteristics of the most commonly applied systems of agricultural production like an ecological, integrated and conventional one. The choice of certain production system is to a great extent determined by the level of production intensity, particularly by input of industrials that improve the yields, which cause the most considerable pressure on the environment. Additionally, the models of organisation in agricultural holdings which practise discussed systems of production, were presented. Author concludes that the integrated system of production has both the biggest chances and capabilities to be implemented.